An Evaluation of Severe Anesthetic-Related Critical Incidents and Risks From the South African Paediatric Surgical Outcomes Study: A 14-Day Prospective, Observational Cohort Study of Pediatric Surgical Patients. (20th December 2021) - Cronjé, Larissa; Torborg, Alexandra M.; Meyer, Heidi M.; Bhettay, Anisa Z.; Diedericks, Johan B.J.S.; Cilliers, Celeste; Kluyts, Hyla-Louise; Mrara, Busisiwe; Kalipa, Mandisa N.; Cloete, Esther; Burke, Annemie; Mogane, Palesa N.; et al.
Abstract : BACKGROUND: Severe anesthetic-related critical incident (SARCI) monitoring is an essential component of safe, quality anesthetic care. Predominantly retrospective data from low- and middle-income countries (LMICs) report higher incidence but similar types of SARCI compared to high-income countries (HIC). The aim of our study was to describe the baseline incidence of SARCI in a middle-income country (MIC) and to identify associated risk for SARCI. We hypothesized a higher incidence but similar types of SARCI and risks compared to HICs. METHODS: We performed a 14-day, prospective multicenter observational cohort study of pediatric patients (aged <16 years) undergoing surgery in government-funded hospitals in South Africa, a MIC, to determine perioperative outcomes. This analysis described the incidence and types of SARCI and associated perioperative cardiac arrests (POCAs). We used multivariable logistic regression analysis to identify risk factors independently associated with SARCI, including 7 a priori variables and additional candidate variables based on their univariable performance. RESULTS: Two thousand and twenty-four patients were recruited from May 22 to August 22, 2017, at 43 hospitals. The mean age was 5.9 years (±standard deviation 4.2). A majority of patients during this 14-day period were American Society of Anesthesiologists (ASA) physical status I (66.4%) or presenting for minor surgery (54.9%). A specialist anesthesiologist managed 59% of cases. These patients were found to be significantly younger ( P < .001) and had higher ASA physical status ( P < .001). A total of 426 SARCI was documented in 322 of 2024 patients, an overall incidence of 15.9% (95% confidence interval [CI], 14.4–17.6). The most common event was respiratory (214 of 426; 50.2%) with an incidence of 8.5% (95% CI, 7.4–9.8). Six children (0.3%; 95% CI, 0.1–0.6) had a POCA, of whom 4 died in hospital. Risks independently associated with a SARCI were age (adjusted odds ratio [aOR] = 0.95; CI, 0.92–0.98; P = .004), increasing ASA physical status (aOR = 1.85, 1, 74, and 2.73 for ASA II, ASA III, and ASA IV–V physical status, respectively), urgent/emergent surgery (aOR = 1.35, 95% CI, 1.02–1.78; P = .036), preoperative respiratory infection (aOR = 2.47, 95% CI, 1.64–3.73; P < .001), chronic respiratory comorbidity (aOR = 1.75, 95% CI, 1.10–2.79; P = .018), severity of surgery (intermediate surgery aOR = 1.84, 95% CI, 1.39–2.45; P < .001), and level of hospital (first-level hospitals aOR = 2.81, 95% CI, 1.60–4.93; P < .001). CONCLUSIONS: The incidence of SARCI in South Africa was 3 times greater than in HICs, and an associated POCA was 10 times more common. The risk factors associated with SARCI may assist with targeted interventions to improve safety and to triage children to the optimal level of care.